Language Planning and Policy Ideologies, Ethnicities, and Semiotic Spaces of Power. - Abdelhay, Ashraf; Makoni, Sinfree; Severo, Cristine (Cambridge Scholars Publisher, 2020)
Language policy is heterogeneous and varies according to its object, levels of intervention, purpose, participants and institutions involved, underlying language ideologies, local contexts, power relations, and historical contexts. This volume offers unique cross-cultural perspectives on language planning and policy in diverse African and Middle Eastern contexts, including South Africa, Bahrain, Sudan, Saudi Arabia, Morocco, Zambia, and Algeria. The African diaspora is also considered, as is the case of Brazil. By bringing together diverse contexts in Africa and the Middle East, this volume en.